DEWAN PERWAKILAN DAERAH (DPD)-RI (REFORMASI FUNGSI, KEDUDUKAN DAN PROSES PEMILIHAN ANGGOTA DPD) - Wirman, Hardi Putra (Alhurriyah, 2009)
DPD has got second periods of their occupation, after general election in 2004, DPD has become one of new department in Indonesia’s government structural, thus Indonesia has bicameral in MPR which consist of DPR and DPD. This department has been regulated in constitution through the third mandement of UUD 1945 has result chapter 22C, 22D and 22E. The existence of this department in Indonesia’s government structural is the way to manifast societies’s opinion and expectation becauce of societies’s disatisfaction to perliement which represent political party. But in the other side, DPD is powerless because it doesn’t have right to have opinion, discuss dan refuse a RUU. Consequently, it needs reformation’s fuction, occupation and election process of DPD, thus it is able to manifest challenges of otonomi daerah in the future.